Antagonistic metabolites produced by the fungus Curvularia sp. BCC52426 against Aspergillus sp. BCC51998. (August 2018) - Bunbamrung, Nantiya; Intaraudom, Chakapong; Dramae, Aibrohim; Boonyuen, Nattawut; Chanthaket, Rungtiwa; Rachtawee, Pranee; Pittayakhajonwut, Pattama
Graphical abstract: Highlights: Four new compounds were isolated from the antagonistic fungus Curvularia sp. BCC52426. The first Z form of chloromonilinic acid B was isolated from natural source. ( Z )-chloromonilinic acid B had anti-TB activity at MIC 50 μg/mL. All tested compounds did not have cytotoxicity at the maximum tested concentration. Abstract: Four previously undescribed compounds, including ( Z )-chloromonilinic acid B (1 ), ( E )-chloromonilinic acid C (2 ), 4-chlorocurvularin (5 ), and 4-chlorocurvularinic acid (6 ), together with four known compounds, ( E )-chloromonilinic acids A and B, pinselin, and anhydromevalonolactone, were isolated from the fungus Curvularia sp. BCC52426. The chemical structures were determined by comparing their NMR spectra to documented spectra of the related compounds and the isolated compounds were also appraised for antimicrobial activity and cytotoxicity.